China's approach to central bank digital currency: Selectively reshaping international financial order? - WANG, Heng (Institutional Knowledge at Singapore Management University, 2022)
China is likely to be the first major economy to issue central bank digital currency (CBDC), the digital version of sovereign currency. China’s CBDC is also known as e-CNY, DC/EP, or digital yuan. ECNY has the potential to profoundly affect the international financial system and order. This article explores the following crucial issues from an international perspective: what are the core features of e-CNY? What is China’s approach to CBDC? What is the long-term sustainability of China’s CBDC approach? This article argues that the role of the state, the potential cross-border use of e-CNY, and China’s proactiveness in international governance are the core features of China’s CBDC. These features contribute to China’s CBDC approach, a possible selective reshaping of international financial order. The article adopts a multifactor analytical framework which explores major economic, political economy, legal and regulatory factors affecting the sustainability of China’s CBDC approach. This framework seeks to promote a holistic understanding of e-CNY’s evolution and its profound implications for international economic governance.